Modal Dasar Kewirausahaan : Pengertian Keterampilan Wirausaha, Modal Insani, Modal Motivasi - Aulia Rahmawati; Osti Riana Br Hutabarat; Tsaniya Raudhatul Jannah (Journal of Islamic Economics and Finance, 2025)
This article aims to provide insight and understanding that entrepreneurial activities also require skills and expertise. Entrepreneurial activities apart from financial capital also require human capital and motivational capital. All of this capital must be present in an individual which is reflected through the character inherent in the person. These characters can actually be the values ​​and norms that Indonesian society has had since ancient times. This research uses the library research method, which involves collecting data sourced from journals and articles. The data collected is then analyzed to understand concepts and theories about basic human capital and entrepreneurial competency provisions that are relevant to the research problem.